Multicultural Education Based on Minangkabau Proverbs to Integrate Democratic Values in History Learning - Fini Fajri Mulyani; Gunartati Gunartati; Ofianto Ofianto; Antonia Soriente; Reyhan Ainun Yafi; Fadilla Syahriani; Mhd Asrian Syah; Tri Zahra Ningsih (STAI Hubbulwathan Duri, 2024)
This research aimed to analyze the implementation of the Minangkabau proverbs as a source of democratic values in history learning. The method used in this research used descriptive qualitative research methods with a phenomenological approach. The sample in this study was selected using a purposive sampling technique consisting of 2 teachers of religious subjects and 8 students from each school. Data collection methods used were interviews, questionnaires and literature studies. The data analysis technique in this research uses Huberman's qualitative analysis technique, which includes stages of data reduction, data presentation, and data verification. The results of this research showed that: 1) Minangkabau proverbs contained deep democratic values and were highly respected by the Minangkabau people; 2) The implementation of multicultural education in instilling democratic values based on Minangkabau proverbial traditions with the stages of moral knowing, moral feeling, and moral action helped students understand, reflect on, and apply democratic values in everyday life.; 3) The implementation of multicultural education in history learning faced several challenges, including students' difficulties in understanding the relationship between the Minangkabau proverb tradition and history, as well as a lack of adequate understanding regarding these proverbs. The implication of this research was that integrating the Minangkabau proverbs tradition as a source of democratic values in history learning could make a significant contribution to the development of students' multicultural education.